Вдосконалення виборчих технологій в сучасній Україні - Карпенко Олександр Олександрович (My University, 2023)
В роботі здійснено історичний огляд розвитку виборчих систем: від радянської епохи до незалежної України. Проаналізовано конституційно-правові основи виборчих технологій в Україні. Визначено сучасний стан та виклики виборчих технологій в Україні. Окреслено вплив цифрових технологій на виборчий процес в Україні. Досліджено міжнародний досвід удосконалення виборчих технологій. Проаналізовано інноваційні підходи до виборчих технологій. Розроблено рекомендації щодо модернізації виборчих технологій в Україні.

The study provides a historical overview of the development of electoral systems: from the Soviet era to independent Ukraine. The constitutional and legal foundations of election technologies in Ukraine are analyzed. The current state and challenges of election technologies in Ukraine are determined. The influence of digital technologies on the election process in Ukraine is outlined. The international experience of improving election technologies was studied. Innovative approaches to election technologies are analyzed. Recommendations for the modernization of election technologies in Ukraine have been developed.
Improvement of election technologies in modern Ukraine
Keywords: виборчі технології; інновації; вибори; фальсифікація; виборча система; міжнародний досвід; модернізація; electoral technologies; innovations; elections; falsification; electoral system; international experience; modernization